Prevalence and clinical characteristics of venous thromboembolism in patients with lung cancer: a systematic review and meta-analysis - Xu, Ying; Wu, Tong; Ren, Xue; Liu, Jing; Zhang, Haibo; Yang, Defu; Yan, Ying; Lv, Dongyang (Frontiers in Oncology, 2024)
Background The prevalence of venous thromboembolism (VTE) is high in patients with cancer and can often present as the first symptom of malignancy. Cancer-associated VTE is one of the most important risk factors contributing to cancer mortality, making its prevention and treatment critical for patients with lung cancer. Methods We systematically searched for observational studies that estimated the prevalence of VTE in patients with lung cancer. A comprehensive search of electronic databases, including PubMed, EMBASE and Cochrane Library, was systematically conducted from database inception through January 21, 2022. The qualities of included studies were assessed in three domains, including patient selection, comparison, and results. Random effects meta-analyses of the prevalence of VTE in lung cancer were conducted using the metaprop procedure. Chi-square test and I2 value were used to evaluate study heterogeneity. Results Thirty-five studies involving 742,156 patients were considered eligible for this study. The pooled prevalence of VTE among patients with lung cancer was 5% (95% CI: 0.043–0.056, P = 0.000). The regional prevalence of VTE was 7% (95% CI: 0.06–0.08; I2 = 99.2%) in North America, 8% (95% CI: 0.06–0.10; I2 = 97.6%) in Asia, 6% (95% CI: 0.04–0.09; I2 = 95.9%) in Europe and 11% (95% CI: 0.07–0.15) in Australasia. Conclusions The prevalence of lung cancer-related VTE is high and region-specific. These results of this review emphasize the importance of understanding the incidence of lung cancer-related VTE and provide argue for VTE screening of patients with lung cancer. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier PROSPERO (CRD42022306400).